Cu4Ti4-oxo clusters functionalized by in situ – generated 2, 2′-biphenolate ligands from the oxidative coupling of phenols. Issue 7 (31st January 2023) - Liu, Xiao-Xue; Wang, Zi-Rui; Chen, Guang-Hui; Li, Qiao-Hong; Tao, Jun; Zhang, Lei
Abstract : A Cu4 Ti4 -oxo cluster stabilized by in situ – formed 2, 2′-biphenolate ligands from the oxidative coupling of phenols was obtained, showing short Cu⋯C contacts. Abstract : Herein, we report a twisted cubic Cu(i )4 Ti(iv )4 -oxo cluster stabilized by in situ – formed 2, 2′-biphenolate ligands from the oxidative coupling of phenols. The 2, 2′-biphenolate-functionalized Cu(i )4 Ti(iv )4 O4 cluster shows short Cu⋯C contacts and exhibits smaller HOMO–LUMO gaps than those of reported Ti(iv )4 O4 .